The Long Pentraxin PTX3 Is an Endogenous Inhibitor of Hyperoxaluria-Related Nephrocalcinosis and Chronic Kidney Disease - Marschner, Julian A.; Mulay, Shrikant R.; Steiger, Stefanie; Anguiano, Lidia; Zhao, Zhibo; Boor, Peter; Rahimi, Khosrow; Inforzato, Antonio; Garlanda, Cecilia; Mantovani, Alberto; Anders, Hans-Joachim (Frontiers in Immunology, 2018)
The long pentraxin 3 (PTX3) exerts a variety of regulatory functions in acute and chronic tissue inflammation. In particular, PTX3 acts as an opsonin for a variety of pathogens and endogenous particles. We hypothesized that PTX3 would exhibit opsonin-like functions towards calcium oxalate crystals, too, and inhibit crystal growth. This process is fundamental in kidney stone disease as well as in hyperoxaluria-related nephrocalcinosis, the paradigmatic cause of chronic kidney disease (CKD) in children with primary hyperoxaluria type I due to genetic defects in oxalate metabolism. Direct effects of PTX3 on calcium oxalate crystals were investigated in chemico by adding recombinant PTX3 to supersaturated calcium and oxalate solutions. PTX3, but not isomolar concentrations of albumin, dose-dependently inhibited crystal growth. In vivo, the PTX3 protein was undetectable in tubular epithelial cells and urine of wild-type mice under physiological conditions. However, its levels increased within 3 weeks of feeding an oxalate-rich diet, an exposure inducing hyperoxaluria-related nephrocalcinosis and CKD in selected mouse strains (male and female C57BL/6N and male Balb/c mice) but not in others (male and female 129SV and CD-1, male and female Balb/c mice). Genetic ablation of ptx3 in nephrocalcinosis un-susceptible B6;129 mice was sufficient to raise the oxalate nephropathy phenotype observed in susceptible strains. We conclude that PTX3 is an endogenous inhibitor of calcium oxalate crystal growth. This mechanism limits hyperoxaluria-related nephrocalcinosis, e.g. in primary or secondary hyperoxaluria, and potentially also in the more prevalent kidney stone disease.